Transcriptomic analysis of differential gene expression reveals an increase in COX2 levels during in vitro canine herpesvirus infection - Kurissio, Jacqueline Kazue [UNESP]; Araujo Junior, Jolt Pessoa [UNESP] (Univ Federal Santa Maria, 2018)
Canine herpesvirus (CaHV-1) affects canids worldwide, causing death in neonates and immunosuppressed hosts. Acute infection by CaHV-1 can cause reproductive. respiratory, and neurological problems in adult animals. Kral pathogenesis and host genes expressions during ofCaHV-1 infection are not clearly understood. In the present study, the transcriptome of canine kidney cell Mardin-Darby (MDCK) infected in vitro with canine herpesvirus was explored. For this. RNA sequencing (RNA-seq) of the samples in different moments during infection was carried out. Subsequently, the transcriptomic analysis genes related to cell activities and process involved to viral cycle infection were evaluated until 32h post-inoculation (pi). Among evaluated genes. was verified a significant and gradative increase of the prostaglandin-endoperoxide synthase 2 (PTGS2) or cyclooxygenase 2 (COX2) gene expression. throughout of infection, though differential gene expression analysis and validated by quantitative reverse transcription PCR (RT-qPCR). High COX2 expression is usually induced in response to inflammation, pathogens or activation of the immune system but can be a viral mechanism to favor viral replication. Thus, COX2 level increase can be a favorable Actor for viral infection with Cahv-I virus and the use of selective COX2 inhibitors may be beneficial for limiting the infection or clinical signs by causing interruption of the viral replication cycle during active infection. Additionally, the regulation genes expression differential verified in this study can contribute to determining important targets for inhibiting canine herpesvirus infection either by cellular or viral mechanisms.
Keywords: transcriptome; herpesvirus CaHV-I; PTGS2; COX2; canine pathogen